Investigação de metodologias para avaliação da resposta de aterramento de linhas de transmissão - Thiago Virgílio de Magalhães Neto (2017)
This work presents results of an experimental investigation about methodologies of measurement of the grounding response of transmission-line tower footing. The tests involved two types of grounding arrangements: concentrate arrangement (small dimension electrodes) and semi-real scale arrangement (relatively short counterpoise wires). First, the impulse response of the grounding was evaluated from the grounding potential rise on electrodes resulting from the application of impulsive currents, whose front times are representative of the currents of first and subsequent return strokes. The main analyzed parameter consisted of the impulse impedance (ZP). The focus of the investigation was the analysis of results provided by the use of so-called 'Artificial Transmission Lines (ATL)' aiming to drastically reducing the distances involved in the measurement. Such units consist of long conductors wrapped around in a PVC pipe. The work concluded that using these units in the current measuring circuit is feasible, once certain cares are observed. In a second approach, the quality of the low-frequency measurements performed by commercial instruments, whose response consists of the ground resistance (RBF), was evaluated. The impact of the level of current provided by the instruments in the grounding response was assessed in the presence of disturbing effects of spurious signals in the soil and polarization at the soil-electrode interface.